Conservation of pine forest biodiversity resources in the districts - Jenni Ria Rajagukguk; Mosses Raissa Graceivan (Journal of diversity in learning (JDIL), 2022)
Biodiversity is the foundation of human life because everyone needs it to sustain life as a source of food, feed, industrial raw materials, cosmetics, and medicines. Indonesia is one of the countries with high biodiversity (fauna and flora), equivalent to Brazil in the Americas and Zaire in Africa or the Democratic Republic of the Congo. Indonesia is also one of the countries with the largest biodiversity in the world, and this biodiversity resource can be utilized by the community to meet the needs of clothing, food, and shelter. One of the reasons for this high level of biodiversity in Indonesia's status as an archipelagic country, with islands located along the equator. The problem is how to conserve pine forest biodiversity resources in Bogor. The research method used is descriptive qualitative and theoretical research methods. The research aims to preserve biodiversity in the Bogor area by implementing legislation at both the central and provincial levels so that it can be utilized by the community to meet the needs of clothing, food, and shelter.